(untitled) (Journal of actual problems of jurisprudence, 2019)
The article discusses a special place and importance of the principles of the criminal justice process in the implementation of the court authorities, and the role of the judiciary in the protection of the rights and freedoms of man and citizen. Keywords: the judiciary, justice, principles of due process, the judicial system, court, judge, sentence.